Are nephrometry scores enough to select patients really fit for nephron sparing surgery? - Porpiglia, Francesco; Amparore, Daniele; Pecoraro, Angela; Checcucci, Enrico (Annals of Translational Medicine, 2019)
In this study, Dahlkamp and colleagues analyzed the role of PADUA and RENAL scores, as calculated by radiologists and urologists, in predicting the risk of conversion to radical nephrectomy (cNE) in a series of patients scheduled for partial nephrectomy.